Investigating EFL Students’ Learning Styles in English for Specific Purposes: A Vark-Based Study on the Fashion Education Context - Sita Nurmasitah; Pudji Astuti; Nabila Luthfionaura; Atika Atika; Joe-Bren L. Consuelo (Universitas Pendidikan Mandalika, 2026)
English for Specific Purposes (ESP) instruction in vocational contexts—particularly in fields such as Fashion Education—has often overlooked students’ diverse learning style preferences, creating a gap between pedagogical approaches and learners’ needs. This study addresses that gap by investigating the learning styles of 40 Fashion Education students using the VARK (Visual, Aural, Read/Write, Kinesthetic) model to inform differentiated ESP pedagogy. Employing a descriptive quantitative method, the study utilized the VARK questionnaire to assess individual learning preferences. Results revealed that 65% of participants demonstrated kinesthetic learning tendencies, while 70% exhibited multimodal profiles. These findings indicate a predominant preference for experiential and blended learning approaches, underscoring the limitations of traditional, text-heavy ESP instruction in vocational settings. The novelty of this study lies in its focus on Fashion Education, a creative and practice-based discipline where learning style alignment is crucial yet underexplored in ESP research. Beyond the local context, the results contribute to international ESP discourse by offering evidence that differentiated and learner-responsive approaches can enhance both engagement and communicative competence. For educators, the study highlights the need to integrate more task-based, hands-on, and multimodal strategies into ESP classrooms to ensure instruction is both industry-relevant and inclusive, thereby improving learning outcomes across vocational education.